2015
DOI: 10.3177/jnsv.61.313
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with DPP-4I Anagliptin or α-GI Miglitol Reduces IGT Development and the Expression of CVD Risk Factors in OLETF Rats

Abstract: Recent cohort studies such as Diabetes Epidemiology: Collaborative Analysis of Diagnostic Criteria in Europe (DECODE) in Europe and FUNAGATA in Japan have demonstrated that postprandial hyperglycemia is a strong independent risk factor for the development of cardiovascular diseases (CVD) in subjects with impaired glucose tolerance (IGT), reflecting pre-diabetic subjects, or type 2 diabetes (1, 2). Furthermore, the Study To Prevent Non-Insulin-Dependent Diabetes Mellitus (STOP-NIDDM) trial reported that suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…BMP7 gene therapy counteracts insulin resistance and obesity ( 46 ). S100A11 expression is reduced during the treatment of impaired glucose tolerance, further reducing the prevalence of T2D ( 47 ). Of these, HBB is a hub gene and is described in the GeneCards database as a protein-coding gene for HBB.…”
Section: Discussionmentioning
confidence: 99%
“…BMP7 gene therapy counteracts insulin resistance and obesity ( 46 ). S100A11 expression is reduced during the treatment of impaired glucose tolerance, further reducing the prevalence of T2D ( 47 ). Of these, HBB is a hub gene and is described in the GeneCards database as a protein-coding gene for HBB.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1b mRNA expression in peripheral leukocytes was reported to be higher in patients with T2DM than in healthy subjects (22). In addition, studies in rodent models have demonstrated that pronounced or moderate postprandial hyperglycemia was associated with the enhanced expression of inflammation-related genes including those encoding TNF-a, IL-1b, S100A8, and S100A9 (17,23,24). The S100A8/A9 heterodimer is also known as a ligand of the receptor for advanced glycation end products (RAGE) and is associated with atherogenesis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Both DM and non‐DM patients who exhibit postprandial hyperglycemia have been reported to have exacerbated insulin resistance and decreased glucagon‐like peptide‐1 levels . These adverse effects on glucose handling and endothelial function can potentially be ameliorated by glycemic variability–reducing drugs, such as dipeptidyl peptidase 4 inhibitors, when taken by nondiabetic patients with high MAGE …”
Section: Discussionmentioning
confidence: 99%